2009
DOI: 10.1016/j.brainresrev.2009.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Plasma biomarkers for mild cognitive impairment and Alzheimer's disease

Abstract: A variety of potential plasma biomarkers for AD and MCI have been identified, however the findings need replication in longitudinal studies. This area of research promises to yield interesting results in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(135 citation statements)
references
References 344 publications
(483 reference statements)
4
125
0
6
Order By: Relevance
“…In addition, a growing focus is on biomarkers which enable detection of the disease in its early stages and will allow for preventative treatment (Song et al 2009). …”
Section: Alzheimer's Disease and The Urgent Need For Early Diagnosis mentioning
confidence: 99%
“…In addition, a growing focus is on biomarkers which enable detection of the disease in its early stages and will allow for preventative treatment (Song et al 2009). …”
Section: Alzheimer's Disease and The Urgent Need For Early Diagnosis mentioning
confidence: 99%
“…Potential neuroimaging techniques that can improve the accuracy to predict conversion to AD are considered as well as potential CSF, urine, blood and genetic biomarkers of AD (continuation). risk factor to MCI conversion to AD (45) associated with the risk of incident AD and dementia (51) and suitable in normal cognitive status conversion to MCI or AD (54,55) associated with higher risk of incident AD and dementia (51) lack of correlation between plasma Aβ levels and plasma homocysteine (50) and Aβ-42 levels in CSF and plasma (57,58) suitable to predict conversion to AD (sensitivity 80% and specificity 82%) (59) strongest correlations in MCI patients (60) strong correlations with oxidized lipoprotein receptor-related protein-1 (sLRP), CSF tau / Aβ-42 ratios and reductions in MMSE scores, risk of MCI and AD (81) correlation with cognitive function (62) useful tool to predict MCI conversion to AD (45,49,50,(63)(64)(65)70) reliable biochemical marker in early stages of AD and in the discrimination from other types of dementia (sensibility 87% and specificity 82%) (66) risk marker for AD in subjects with MCI (67) useful in prediction of incident impairment in asymptomatic individuals (68) predictive of cognitive decline and hippocampal volume loss (69) candidate biomarkers for AD and the predementia condition of MCI (73) related to familial AD (prevalence around 0,1%) (45) risk factor for AD (45) risk factor for sporadic AD (45) involved in familial AD and other neurodegenerative diseaes (80,81) (myo-inositol/creatine ratio) in the cortical area of right parietal lobe in MCI subjects predicted the conversion to AD with sensitivity 70% and specificity 85%.…”
Section: Challenges In the Discovery Of Potential Biomarkers In Alzhementioning
confidence: 99%
“…In familial AD cases, total Aβ and Aβ1-42 plasma levels are elevated [79] . In sporadic AD, several cross-sectional studies report no significant difference in plasma Aβ concentrations in general compared to controls [79][80][81][82] . Unfortunately, longitudinal studies have shown high data variability.…”
Section: Aβ Peptidesmentioning
confidence: 99%
“…BACE cleaves APP and releases a large N-terminal fragment (sAPPβ). The membrane-anchored frag- [73,75] Decreased [65] β-amyloid (Aβ) Decreased [45,46] No difference [79][80][81][82] No difference [47] Aβ1- 40 No difference [24] No difference [83] Increased [84] Decreased [85] Aβ1- 42 Decreased [24] Increased [83] -Aβ1-42/Aβ1-40 ratio Decreased [48] No difference [83] Decreased [78,84,86] APP ratio --Decreased [90][91][92][93] Ubiquitin Increased [24] No difference [148] BACE1 Increased [67] --Cholesterol -Decreased [94,95] Increased [96][97][98] 24S-hydroxycholesterol Increased [102] No difference [103] Decreased [104] Homocysteine -Increased [106,107,109] Epidermal growth factor -Decreased [111] Decreased [93] Increased [112] Glial cell line-derived growth factor -Decreased [111] No difference …”
Section: Aβ1-42mentioning
confidence: 99%